2001
DOI: 10.1002/chin.200112039
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Lipase‐Catalyzed Reactions in Ionic Liquids.

Abstract: biochemical syntheses, microbiological syntheses biochemical syntheses, microbiological syntheses O 0035 -039Lipase-Catalyzed Reactions in Ionic Liquids.-Preliminary studies concerning transesterification of ethyl butanoate, transesterification and ammonolysis of ethyl octanoate and epoxidation of cyclohexene are presented.The reactions are carried out with Candida antarctica lipase in the presence of 1-butyl-3-ethylimidazolium tetrafluoroborate or hexafluorophosphate. The rates are comparable with or better t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 1 publication
0
18
0
Order By: Relevance
“…[8][9][10][11] Furthermore, many liquid-liquid phase equilibrium systems such as IL/water and IL/ organic solvent systems have been presented; this indicates the possibility of utilizing ILs as reaction or extraction solvents. [12][13][14][15] For example, it has been shown that 1-alkyl-3-methylimidazolium bis(trifluoromethane sulfonyl)amide ([C n mim][NTf 2 ]), a typical hydrophobic IL, can be used for the extraction of aromatic compounds from aliphatic hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] Furthermore, many liquid-liquid phase equilibrium systems such as IL/water and IL/ organic solvent systems have been presented; this indicates the possibility of utilizing ILs as reaction or extraction solvents. [12][13][14][15] For example, it has been shown that 1-alkyl-3-methylimidazolium bis(trifluoromethane sulfonyl)amide ([C n mim][NTf 2 ]), a typical hydrophobic IL, can be used for the extraction of aromatic compounds from aliphatic hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%
“…Biocatalysis in ionic liquids was first reported in Cull et al (2000) and Lau et al (2000) and studies that deal with this theme claim that these systems show a higher selectivity, higher rate and greater enzyme stability. In biodiesel production, the support of enzymes in ionic liquids has been developed aiming to overcome problems associated with conventional enzymatic transesterification, such as enzyme deactivation by some alcohols, particularly methanol, and blockage of active sites of the enzyme by glycerol, which decreases their activity and inhibits the reuse of the biocatalyst.…”
Section: Ionic Liquids As Supports For Enzymatic Catalysismentioning
confidence: 99%
“…The use of enzymes, especially lipases, in ionic liquids, has demonstrated many advantages, such as high conversion rates, good enantioselectivity, better recoverability and recyclability. For example, the stability of lipases such as CaLB [13][14][15][16] and Pseudomonas cepacia lipase (PcL) [15,17] are catalytically active in imidazolium and pyridinium ILs containing BF 4´, PF 6´a nd Tf 2 N´ [14]. [OmPy][BF 4 ] provide high enantioselectivity to hesperidinase when used as co-solvent in the enzymatic conversion of rutin to isoquercitrin.…”
Section: Introductionmentioning
confidence: 99%